Public-Private Collaboration in Tourism. Institutional Capacities in Local Tourism Management Partnerships in Argentina - Russo, Nicolas Esteban; Darmohraj, Adrián (Revista del CLAD Reforma y Democracia, 2016)
Local Tourism Institutional Public-Private Partnerships (IPPPs) are promoted in Argentina as a best practice in local governance given their potential to stimulate tourism growth by private sector participation in tourism policies. However, few studies have focused on the capacities or the performance of that type of collaborative arrangements.The main purpose of this qualitative, exploratory and descriptive research is to identify and describe the main institutional capacities of Local Tourism IPPPs that enhance their performance in terms of outputs, outcomes and impacts. Through a comparative case study of two Local Tourism IPPPs in Argentina, Confederación Agencia de Desarrollo Ushuaia Bureau and Instituto Mixto de Turismo de Tandil, the study identifies three dimensions of institutional capacity: the rules of the game; the organizational development needed to manage collaboration; and the network of public and private actors. The findings suggest that the three dimensions are interrelated, and both cases show different levels of institutional capacities along the identified dimensions.This research shows that even when the growth of public-private collaboration in tourism at the local level in Argentina is indisputable, collaboration is quite complex given the type of stakeholders involved and their vested interests. In that context, the setting of rules that determine clear roles for partnership members and balance economic contribution with stakeholder participation seems to be a crucial point to align public and private interests. The Legal Form chosen to perform collaboration has a major impact on organizational performance. Good relational skills are key to building consensus among members of the IPPP and to establishing strong links with provincial and national-level actors whose cooperation is relevant for the achievement of partnership goals.
Keywords: Public Private Association; Administrative Capability; Tourism Policy; Municipalities; Case Analysis; Argentina